2018
DOI: 10.2174/1570162x16666180730144455
|View full text |Cite
|
Sign up to set email alerts
|

Structural Barriers to Pre-exposure Prophylaxis Use Among Young Sexual Minority Men: The P18 Cohort Study

Abstract: Background: Despite decreasing rates of HIV among many populations, HIV-related health disparities among gay, bisexual and other men who have sex with men persist, with disproportional percentages of new HIV diagnoses among racial and ethnic minority men. Despite increasing awareness of HIV pre-exposure prophylaxis (PrEP), PrEP use remains low. In addition to exploring individual-level factors for this slow uptake, structural drivers of PrEP use must also be identified in order to maximize the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…Participants with greater concerns around talking with their provider about their sexual behaviors were less likely to use PrEP [191] Online surveys and focus groups of adolescents (N = 56), most of whom were cis male (95%) and identified as gay (79%)…”
Section: History Of Substance Abusementioning
confidence: 99%
“…Participants with greater concerns around talking with their provider about their sexual behaviors were less likely to use PrEP [191] Online surveys and focus groups of adolescents (N = 56), most of whom were cis male (95%) and identified as gay (79%)…”
Section: History Of Substance Abusementioning
confidence: 99%
“…A surprising finding was the lack of open discussion that was experienced during consultations. From the perspective of the service user, conversations around sexual behaviour were missed as they were seen to be difficult, [62,67,80] uncomfortable, [61,97] or as a consequence of the service providers' failure to take complete histories [56,60,68,78,79,86,96]. Some studies reported the lack of disclosure of sexual activity [80,82,99] and PrEP use [80,82,99], due to concerns for privacy and confidentiality, perceived stigma, fear of negative repercussions and embarrassment.…”
Section: Theme Two: Prep Prescriber Experiences Therapeutic Alliancementioning
confidence: 99%
“…A range of solutions for improving the relationship between the service users and providers were offered in the studies. These included having gay-friendly service providers and affirmative training, [77,79,80,94,100] improving long-term communication to build trust, [62,67,92,94,95,101] developing patient-centred care, [92] increasing service provider knowledge and awareness of PrEP, [62,96,101] and encouraging wider health discussions [62,78]. Key solutions included the routinisation of PrEP prescribing with electronic health record systems that could be used 'to identify potential PrEP candidates… and follow up-care', [62] and the delivery of PrEP using a shared decision-making approach between the patient and service provider, as proposed by Calabrese et al [68] and Krakower et al [57].…”
Section: Theme Two: Prep Prescriber Experiences Therapeutic Alliancementioning
confidence: 99%
See 1 more Smart Citation
“… 23 Moreover, PrEP-related out-of-pocket costs can vary widely depending on one's insurance, 24 and high PrEP-related costs are a barrier to PrEP use. 25–27 PrEP reduces HIV transmission for sexual encounters by >90% and for injection drug use by >70%. 28 Each HIV infection that is averted saves approximately $400,000.…”
Section: Introductionmentioning
confidence: 99%